Man, be ethical-moral - Castagnetti Morini, Antonio (2016)
The human person is the obligatory path for the foundation of ethical judgment. The human being, created by God, is the ontological and objective foundation of the Moral Theology of the person. Lost that objectivity, says Ramón Flecha Andrés, author of several books of Moral Theology, a criterion has been eagerly sought to emphasize, as on land, the moral assessment of human behaviors. Suspicion of objective truth would force in recent centuries to appeal to a norm agreed upon by human beings and supported by the scaffolding of legal systems. (...) Morality is characteristic of human beings. Morality is "human" in many ways. It is people who behave morally. But it is morality that shapes "humanity." Hence, it is necessary to affirm again and again the centrality of the human person in moral reflection; and that, at least, in two inevitable and complementary senses: as an objective of morality: (fr. Ramón Flecha A Moral of the person).